Qualitative Acceptance Model of Augmented Reality from the Perspective of Personalists - Sabrina Romina Sorko* (Tehnički Glasnik, 2020)
Smart devices and the corresponding new technologies have established themselves within our society. Since the release of the smartphone game Pokémon Go, the field of augmented reality (AR) - the enrichment of reality with information, realized by smart devices such as tablets, data glasses or smartphones - has been experiencing an upswing. Additionally, the industry is starting to integrate AR applications to increase efficiency. In this respect, HR managers play a key role in the implementation of such technology. They maintain direct contact with employees, have an overview of the entire company and thus are often responsible for change processes. The paper analyses the potential of AR within a company from a personalist’s point of view and discusses critical factors both in theory and practice. The paper validates the technological possibilities and shows results from a qualitative analysis from focus group discussions. The qualitative acceptance model displays factors influencing the implementation of AR.